Compassionate communication levels of nursing students: Predictive role of empathic skills and nursing communication course. Issue 1 (3rd October 2021) - Öztürk, Ayfer; Kaçan, Havva
Abstract: Purpose: This study aims to determine the compassionate communication levels of nursing students and the predictive roles of empathic skills and nursing communication courses. Design and Methods: This descriptive study was conducted with 430 nursing students and data were analyzed using a descriptive information form, Compassionate Communication Scale (CCS), and Empathic Skill Scale (ESS). Findings: A positive relationship was found between the students' ESS and CCS scores ( r  = .23 p  = 0.001). Empathic skills ( β  = 0.43, p  = 0.001), predicted compassionate communication ( β  = 0.23, p  = 0.001), compassionate conversation (β = 0.43, p  = 0.001),  and compassionate touch ( β  = 0.18, p  = 0.001). Practice Implications: Skills of compassion and empathy positively affect each other; therefore, it is important to adopt strategies that strengthen the empathic skills of nursing students during academic education and to include empathy and compassion in the curriculum.